Packaging film for aquatic products and preparation method thereof
By mixing titanium dioxide and zinc acetate with triethanolamine, the oxides of titanium and zinc are prepared, combined with lecithin and other components to form supported liposomes, which are used to prepare aquatic product packaging films, and the production of antibacterial hydrogen gas is solved by catalyzing light. Problems of aquatic product oxidation and microbial spoilage, extending shelf life and reducing costs.
Patent Information
- Application Number
- CN202411483607.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-10-23
AI Technical Summary
Aquatic products are prone to oxidation and microbial corruption, resulting in deterioration of refrigeration quality, and it is difficult for the prior art to effectively utilize hydrogen for freshness.
Titanium dioxide and zinc acetate are mixed with triethanolamine, and then grinding and roasting to obtain oxides of titanium and zinc, combined with lecithin, cholesterol and ethyl butyrate, forming liposomes, which are supported in the membrane matrix, and are catalyzed to produce antibacterial Hydrogen gas destroys the growth environment of bacteria.
Under light conditions, water vapor is slowly decomposed to produce antibacterial hydrogen, prolong the shelf life of aquatic products, stabilize the lock-in of titanium and zinc oxides, ensure antibacterial effect, reduce costs, and avoid the introduction of impurities.
Smart Images

Figure CN119176962A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of film materials, and in particular relates to a packaging film for aquatic products and a preparation method thereof. Background Art
[0002] Aquatic products are rich in unsaturated fatty acids and other substances, and have high nutritional value. However, highly unsaturated fatty acids are very easy to oxidize and cause rancidity. In addition, environments suitable for microbial growth such as high moisture content and neutral pH values are also very easy to cause microbial corruption of aquatic products, reducing nutritional quality and causing food waste. Lipid oxidation and microbial reproduction are important reasons for the deterioration of the quality of aquatic products during refrigeration. Therefore, based on active packaging, the development of environmentally friendly aquatic product preservation technology that is both effective and safe has become a current research hotspot. Many studies have confirmed that hydrogen can improve the antioxidant capacity of organisms through different mechanisms of action, effectively reduce the deterioration and degree of corruption of the sensory quality of aquatic products, maintain their storage color, flavor, and nutritional quality, and has potential application value in improving food safety. How to effectively use hydrogen in actual aquatic product preservation requires further research. Summary of the invention
[0003] The present invention mainly provides a packaging film for aquatic products that can utilize the high water content of aquatic products to produce hydrogen and maintain the storage quality of aquatic products. The technical solution is as follows:
[0004] A method for preparing a packaging film for aquatic products comprises the following steps:
[0005] a. Mix titanium dioxide and zinc acetate, add triethanolamine at room temperature, grind until the triethanolamine is completely melted and continue grinding for 5 to 20 minutes; then disperse them in anhydrous ethanol, heat to 60 to 80°C, let stand for 12 to 20 hours, evaporate the ethanol, and roast at 400 to 550°C for 1 to 3 hours to obtain titanium and zinc oxides;
[0006] b. Mixing titanium and zinc oxides with triethanolamine; dissolving lecithin, cholesterol and ethyl butyrate in ethanol, and then adding titanium and zinc oxides mixed with triethanolamine to fully disperse to obtain a dispersion; evaporating the ethanol in the dispersion under reduced pressure, adding water to hydrate; and obtaining a liposome liquid after ultrasonication;
[0007] c. When preparing the membrane matrix, add liposome liquid and obtain the packaging film after drying.
[0008] Furthermore, the mass ratio of titanium dioxide to zinc acetate in step a is 1:2-5; the mass ratio of triethanolamine to zinc acetate in step a is 1:1.5-2.5; and the concentration of zinc acetate in anhydrous ethanol in step a is 0.02-0.1 g / mL.
[0009] Furthermore, the mass ratio of cholesterol to lecithin in step b is 1:4-6; the mass ratio of ethyl butyrate to lecithin is 1:15-20; the mass ratio of titanium and zinc oxides to lecithin is 1:8-12; the mass ratio of triethanolamine to titanium and zinc oxides in step b is 1:5-8.
[0010] Furthermore, the steps of removing ethanol from the dispersion under reduced pressure and adding water for hydration are: removing ethanol under reduced pressure at 40-60° C., then adding water to restore the dispersion to its original volume, and rotating for hydration at normal pressure for 0.3-1 h.
[0011] Furthermore, the drying in step c is to dry until the mass no longer changes, and then control the temperature at 80-90° C. to continue drying for 0.5-2 hours.
[0012] Furthermore, the step of preparing the membrane matrix in step c includes: placing gelatin and chitosan in a liposome liquid, mixing them thoroughly at 60-80° C. to obtain a membrane matrix liquid; ultrasonically degassing the membrane matrix liquid, then pouring it into a mold, drying it at 40-50° C. for 3-5 hours, and then heating it to 80-90° C. and continuing to dry it for 10-30 minutes.
[0013] Furthermore, the mass ratio of gelatin to chitosan is 1:0.5-2; and the concentration of gelatin in the membrane matrix fluid is 0.05-0.1 g / mL.
[0014] Furthermore, the sufficient mixing time is 15 to 30 minutes.
[0015] A packaging film for aquatic products prepared by the above-mentioned preparation method comprises a film matrix and liposomes loaded on the film matrix, and titanium and zinc oxides contained in the liposomes.
[0016] Furthermore, the components of the membrane matrix include one or more of polylactic acid, gelatin, chitosan, dextran, polyvinyl alcohol or sodium alginate.
[0017] By adopting the above scheme, the method of the present invention has the following advantages:
[0018] 1. Under light conditions, the titanium and zinc oxides of the packaging film of the present invention can synergistically catalyze and decompose the large amount of water vapor produced by aquatic products slowly, destroying the high humidity environment for the growth of pathogens, and at the same time produce antibacterial hydrogen. The concentration increases with the storage time and light intensity under closed conditions, adapting to the antibacterial strength requirements of different storage conditions.
[0019] 2. The present invention grinds titanium dioxide and zinc acetate together, utilizing the greater polarity of titanium dioxide to cooperate with hygroscopic zinc acetate to produce surface hydroxyl groups, so that titanium dioxide and zinc acetate are fully and evenly dispersed and combined during the grinding process.
[0020] 3. The present invention utilizes the melting point of triethanolamine close to room temperature to promote the miniaturization of the particle size of zinc acetate and titanium dioxide in the solid state and also promote the full mixing of the two. During the grinding process, the triethanolamine gradually changes into a liquid state, realizing the change of the triethanolamine concentration in the system from low to high, so that the triethanolamine and the dispersed titanium dioxide form a uniform coating, and the contact with the zinc acetate is more sufficient, thereby reducing the amount of ethanol used, shortening the gelation time, and saving costs.
[0021] 4. After the liposomes are loaded on the membrane matrix, the present invention can remove ethyl butyrate by extending the drying time, thereby causing ruptures in the liposomes to facilitate contact between zinc and titanium oxides and the outside world, forming channels for hydrogen production and release.
[0022] 5. The triethanolamine of the present invention can be used for the dispersion of titanium dioxide and the decomposition of zinc acetate. It can be used for the full dispersion of titanium and zinc oxides in the preparation of liposomes and can also be used as an emulsifier in film formation, thus achieving multiple uses of one material and greatly reducing costs. The single raw material also avoids the introduction of impurities and separation costs.
[0023] 6. The titanium and zinc oxides of the present invention are firmly locked on the membrane, dispersed evenly and not easy to fall off, which solves the problem of easy agglomeration of titanium dioxide in the system and ensures the stability of the antibacterial effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a sample photo of the packaging film of Example 1;
[0025] Figure 2 is a sample photo of the packaging film of Example 2;
[0026] Figure 3 It is a comparison chart of the antibacterial effects of various embodiments and comparative examples. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Embodiment 1:
[0029] (1) 1 g of titanium dioxide and 5 g of zinc acetate were mixed, 1.5 g of triethanolamine was added at room temperature, and the mixture was ground until the triethanolamine was completely melted and then continued to be ground for 10 min; then the mixture was placed in 100 mL of anhydrous ethanol and fully dispersed, the mixture was heated to 70° C., allowed to stand for 16 h, the ethanol was evaporated, and then calcined at 500° C. for 12 h to obtain titanium and zinc oxides;
[0030] (2) Mix 0.5 g of titanium and zinc oxides with 0.1 g of triethanolamine; dissolve 5 g of egg yolk lecithin, 1 g of cholesterol, and 0.25 g of ethyl butyrate in ethanol, then add the titanium and zinc oxides mixed with triethanolamine and fully disperse them to obtain a dispersion; evaporate the ethanol under reduced pressure at 40 to 60° C., then add water to restore the original volume of the dispersion, and rotate and hydrate at normal pressure for 0.5 h; after ultrasonication, a liposome solution is obtained;
[0031] (3) 2 g of gelatin and 1 g of chitosan were placed in 20 mL of liposome liquid and mixed thoroughly at 70°C to obtain a membrane matrix liquid; the membrane matrix liquid was ultrasonically degassed, and then 16 mL was poured into a 13 cm × 13 cm square mold, dried at 400°C for 3 h, and then heated to 90°C for another 10 min. Figure 1 It can be seen that the surface of the obtained membrane sample is smooth, dense and uniform, and the higher zinc content makes it light yellow.
[0032] Embodiment 2:
[0033] (1) 1 g of titanium dioxide and 2 g of zinc acetate were mixed, 1.5 g of triethanolamine was added at room temperature, and the mixture was ground until the triethanolamine was completely melted and then continued to be ground for 10 min; then the mixture was placed in 100 mL of anhydrous ethanol and fully dispersed, the mixture was heated to 70° C., allowed to stand for 16 h, the ethanol was evaporated, and then calcined at 500° C. for 12 h to obtain titanium and zinc oxides;
[0034] (2) Mix 0.5 g of titanium and zinc oxides with 0.1 g of triethanolamine; dissolve 5 g of egg yolk lecithin, 1 g of cholesterol, and 0.25 g of ethyl butyrate in ethanol, then add the titanium and zinc oxides mixed with triethanolamine and fully disperse them to obtain a dispersion; evaporate the ethanol under reduced pressure at 40 to 60° C., then add water to restore the original volume of the dispersion, and rotate and hydrate at normal pressure for 0.5 h; after ultrasonication, a liposome solution is obtained;
[0035] (3) 2 g of gelatin and 1 g of chitosan were placed in 20 mL of liposome liquid and mixed thoroughly at 70°C to obtain a membrane matrix liquid; the membrane matrix liquid was ultrasonically degassed, and then 16 mL was poured into a 13 cm × 13 cm square mold, dried at 400°C for 3 h, and then heated to 90°C for another 10 min. Figure 2 It can be seen that the surface of the obtained membrane sample is smooth, dense, uniform and transparent.
[0036] Embodiment 3:
[0037] (1) 1 g of titanium dioxide and 5 g of zinc acetate were mixed, 1.5 g of triethanolamine was added at room temperature, and the mixture was ground until the triethanolamine was completely melted and then continued to be ground for 10 min; then the mixture was placed in 100 mL of anhydrous ethanol and fully dispersed, the mixture was heated to 70° C., allowed to stand for 16 h, the ethanol was evaporated, and then calcined at 500° C. for 12 h to obtain titanium and zinc oxides;
[0038] (2) Mix 0.5 g of titanium and zinc oxides with 0.06 g of triethanolamine; dissolve 5 g of egg yolk lecithin, 1 g of cholesterol, and 0.25 g of ethyl butyrate in ethanol, then add the titanium and zinc oxides mixed with triethanolamine and fully disperse them to obtain a dispersion; evaporate the ethanol under reduced pressure at 40 to 60° C., then add water to restore the original volume of the dispersion, and rotate and hydrate at normal pressure for 0.5 h; after ultrasonication, a liposome solution is obtained;
[0039] (3) 2 g of gelatin and 1 g of chitosan were placed in 20 mL of liposome liquid and mixed thoroughly at 70°C to obtain a membrane matrix liquid; the membrane matrix liquid was ultrasonically degassed, and then 16 mL was poured into a 13 cm × 13 cm square mold, dried at 400°C for 3 h, and then heated to 90°C and continued to dry for 10 min.
[0040] Embodiment 4:
[0041] (1) 1 g of titanium dioxide and 5 g of zinc acetate were mixed, 1.5 g of triethanolamine was added at room temperature, and the mixture was ground until the triethanolamine was completely melted and then continued to be ground for 10 min; then the mixture was placed in 100 mL of anhydrous ethanol and fully dispersed, the mixture was heated to 70° C., allowed to stand for 16 h, the ethanol was evaporated, and then calcined at 500° C. for 12 h to obtain titanium and zinc oxides;
[0042] (2) Mix 0.5 g of titanium and zinc oxides with 0.1 g of triethanolamine; dissolve 5 g of egg yolk lecithin, 1 g of cholesterol, and 0.34 g of ethyl butyrate in ethanol, then add the titanium and zinc oxides mixed with triethanolamine and fully disperse them to obtain a dispersion; evaporate the ethanol under reduced pressure at 40 to 60° C., then add water to restore the original volume of the dispersion, and rotate and hydrate at normal pressure for 0.5 h; after ultrasonication, a liposome solution is obtained;
[0043] (3) 2 g of gelatin and 1 g of chitosan were placed in 20 mL of liposome liquid and mixed thoroughly at 70°C to obtain a membrane matrix liquid; the membrane matrix liquid was ultrasonically degassed, and then 16 mL was poured into a 13 cm × 13 cm square mold, dried at 400°C for 3 h, and then heated to 90°C and continued to dry for 10 min.
[0044] Embodiment 5:
[0045] (1) 1 g of titanium dioxide and 5 g of zinc acetate were mixed, 1.5 g of triethanolamine was added at room temperature, and the mixture was ground until the triethanolamine was completely melted and then continued to be ground for 10 min; then the mixture was placed in 100 mL of anhydrous ethanol and fully dispersed, the mixture was heated to 70° C., allowed to stand for 16 h, the ethanol was evaporated, and then calcined at 500° C. for 12 h to obtain titanium and zinc oxides;
[0046] (2) Mix 0.5 g of titanium and zinc oxides with 0.1 g of triethanolamine; dissolve 5 g of egg yolk lecithin, 1 g of cholesterol, and 0.25 g of ethyl butyrate in ethanol, then add the titanium and zinc oxides mixed with triethanolamine and fully disperse them to obtain a dispersion; evaporate the ethanol under reduced pressure at 40 to 60° C., then add water to restore the original volume of the dispersion, and rotate and hydrate at normal pressure for 0.5 h; after ultrasonication, a liposome solution is obtained;
[0047] (3) 2 g of gelatin and 4 g of chitosan were placed in 20 mL of liposome liquid and mixed thoroughly at 70°C to obtain a membrane matrix liquid; the membrane matrix liquid was ultrasonically degassed, and then 16 mL was poured into a 13 cm × 13 cm square mold, dried at 400°C for 3 h, and then heated to 90°C and continued to dry for 10 min.
[0048] Embodiment 6:
[0049] (1) 1 g of titanium dioxide and 5 g of zinc acetate were mixed, 1.5 g of triethanolamine was added at room temperature, and the mixture was ground until the triethanolamine was completely melted and then continued to be ground for 10 min; then the mixture was placed in 100 mL of anhydrous ethanol and fully dispersed, the mixture was heated to 70° C., allowed to stand for 16 h, the ethanol was evaporated, and then calcined at 500° C. for 12 h to obtain titanium and zinc oxides;
[0050] (2) Mix 0.5 g of titanium and zinc oxides with 0.1 g of triethanolamine; dissolve 5 g of egg yolk lecithin, 1 g of cholesterol, and 0.25 g of ethyl butyrate in ethanol, then add the titanium and zinc oxides mixed with triethanolamine and fully disperse them to obtain a dispersion; evaporate the ethanol under reduced pressure at 40 to 60° C., then add water to restore the original volume of the dispersion, and rotate and hydrate at normal pressure for 0.5 h; after ultrasonication, a liposome solution is obtained;
[0051] (3) 2 g of gelatin and 1 g of chitosan were placed in 40 mL of liposome liquid and mixed thoroughly at 70°C to obtain a membrane matrix liquid; the membrane matrix liquid was ultrasonically degassed, and then 16 mL was poured into a 13 cm × 13 cm square mold, dried at 400°C for 3 h, and then heated to 90°C and continued to dry for 10 min.
[0052] Embodiment 7:
[0053] (1) 1 g of titanium dioxide and 5 g of zinc acetate were mixed, 1.5 g of triethanolamine was added at room temperature, and the mixture was ground until the triethanolamine was completely melted and then continued to be ground for 10 min; then the mixture was placed in 100 mL of anhydrous ethanol and fully dispersed, the mixture was heated to 70° C., allowed to stand for 16 h, the ethanol was evaporated, and then calcined at 500° C. for 12 h to obtain titanium and zinc oxides;
[0054] (2) Mix 0.5 g of titanium and zinc oxides with 0.1 g of triethanolamine; dissolve 5 g of egg yolk lecithin, 1 g of cholesterol, and 0.25 g of ethyl butyrate in ethanol, then add the titanium and zinc oxides mixed with triethanolamine and fully disperse them to obtain a dispersion; evaporate the ethanol under reduced pressure at 40 to 60° C., then add water to restore the original volume of the dispersion, and rotate and hydrate at normal pressure for 0.5 h; after ultrasonication, a liposome solution is obtained;
[0055] (3) 2 g of gelatin and 1 g of chitosan were placed in 20 mL of liposome liquid and mixed thoroughly at 70°C to obtain a membrane matrix liquid; the membrane matrix liquid was ultrasonically degassed, and then 16 mL was poured into a 13 cm × 13 cm square mold, dried at 400°C for 3 h, and then heated to 90°C for another 30 min.
[0056] Comparative Example 1:
[0057] 2 g of gelatin and 4 g of chitosan were placed in 20 mL of water and mixed thoroughly at 70°C to obtain a membrane matrix liquid; the membrane matrix liquid was ultrasonically degassed, and then 16 mL was poured into a 13 cm × 13 cm square mold, dried at 400°C for 3 h, and then heated to 90°C and continued to dry for 10 min.
[0058] Preparation and testing of samples of the embodiments:
[0059] The scallop scallops were completely removed from the shell, and the average mass of the scallops was (14.8±0.9) g. The scallops were randomly divided into 8 groups according to the embodiments and comparative examples, each group containing 15 scallops, and each group was wrapped with the packaging film of each embodiment and comparative example. Each group was stored at 4°C, irradiated with a xenon lamp to simulate visible light for 4 hours every day, and samples were collected on the 0th, 3rd, 6th, 9th and 12th days for index detection. Six scallops were randomly selected from each group. The total colony count of the sample was determined according to GB 4789.2-2022 "National Food Safety Standard for Food Microbiological Examination of Total Colony Count Determination". 5.0g of minced sample and 45mL of sterile 0.85% NaCl solution were added to a sterile homogenizing bag, and the mixture was homogenized and beaten at a speed of 8 times / s for 90s to obtain an extract. The extract was serially diluted 10 times with sterile 0.85% NaCl solution, and then 1 mL of the dilution was inoculated into plate count agar, and the total number of colonies was calculated after incubation at 30°C for 72 h.
[0060] The results are as follows:
[0061]
[0062] Combined with the above table Figure 3 It can be seen that the total colony count of the comparative example 1 group without liposome loading increased significantly, reaching 5.92lg (CFU / g) on the 6th day, exceeding the total colony count of each embodiment for 12 days, and the colony count of the scallops wrapped by the packaging film of the present invention was still lower than the limit value of 7.0lg (CFU / g) at 12 days, indicating that the packaging film of the present invention can significantly extend the shelf life of aquatic products. The total colony count growth rate of Example 1 using more zinc acetate is slower than that of Example 2, but the degree of relaxation is not as good as the increase in the content of zinc acetate, indicating that the oxides of zinc and titanium can synergistically promote hydrogen production, and only increasing zinc cannot effectively improve the antibacterial ability of the packaging film. The antibacterial effect of Example 3 is not as good as that of Example 1, which may be that less triethanolamine is not conducive to the full dispersion of the oxides of zinc and titanium, affecting the antibacterial effect of the packaging film. Example 4 adds more ethyl butyrate compared to Example 1, but the total colony count growth rate is faster than that of Example 1, which may be that too much ethyl butyrate easily affects the integrity of the liposomes, and affects the integrity of the film after volatilization in the later stage of film drying. The growth rate of the total number of colonies in Example 5 is not as fast as that in Example 1, indicating that more chitosan can improve the antibacterial ability of the membrane and the water vapor barrier performance of gelatin. The amount of liposome liquid added in Example 6 was increased to 40 mL, but its antibacterial effect was not as expected. It may be that too many liposomes easily affect the strength of the membrane and affect the water vapor permeability. More zinc and titanium oxides increase the hydrogen production rate, but the reduction of water is not conducive to hydrogen production. The drying time of Example 7 is longer than that of Example 1, and the total number of colonies at 12 days decreased.
[0063] For those skilled in the art, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all of these changes and deformations should fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a packaging film for aquatic products, characterized in that: The following steps are involved: a. Mix titanium dioxide and zinc acetate, add triethanolamine at room temperature, grind until the triethanolamine is completely melted and continue grinding for 5 to 20 minutes; then disperse them in anhydrous ethanol, heat to 60 to 80°C, let stand for 12 to 20 hours, evaporate the ethanol, and roast at 400 to 550°C for 1 to 3 hours to obtain titanium and zinc oxides; b. Mixing titanium and zinc oxides with triethanolamine; dissolving lecithin, cholesterol and ethyl butyrate in ethanol, and then adding titanium and zinc oxides mixed with triethanolamine to fully disperse to obtain a dispersion; evaporating the ethanol in the dispersion under reduced pressure, adding water to hydrate; and obtaining a liposome liquid after ultrasonication; c. When preparing the membrane matrix, add liposome liquid and obtain the packaging film after drying.
2. The method for preparing a packaging film for aquatic products according to claim 1, characterized in that: The mass ratio of titanium dioxide to zinc acetate in step a is 1:2-5; the mass ratio of triethanolamine to zinc acetate in step a is 1:1.5-2.5; the concentration of zinc acetate in anhydrous ethanol in step a is 0.02-0.1 g / mL.
3. The method for preparing a packaging film for aquatic products according to claim 1, characterized in that: The mass ratio of cholesterol to lecithin in step b is 1:4-6; the mass ratio of ethyl butyrate to lecithin is 1:15-20; the mass ratio of titanium and zinc oxides to lecithin is 1:8-12; the mass ratio of triethanolamine to titanium and zinc oxides in step b is 1:5-8.
4. The method for preparing a packaging film for aquatic products according to claim 1, characterized in that: The steps of removing ethanol from the dispersion under reduced pressure and adding water for hydration are: removing ethanol under reduced pressure at 40-60° C., then adding water to restore the dispersion to its original volume, and rotating at normal pressure for 0.3-1 h.
5. The method for preparing aquatic product packaging film according to claim 1, characterized in that: The drying in step c is to dry until the mass no longer changes, and then control the temperature at 80-90° C. to continue drying for 0.5-2 hours.
6. The method for preparing aquatic product packaging film according to claim 1, characterized in that: The step of preparing the membrane matrix in step c comprises: placing gelatin and chitosan in a liposome liquid, mixing them thoroughly at 60-80° C. to obtain a membrane matrix liquid; ultrasonically degassing the membrane matrix liquid, then pouring it into a mold, drying it at 40-50° C. for 3-5 hours, then heating it to 80-90° C. and continuing to dry it for 10-30 minutes.
7. The method for preparing a packaging film for aquatic products according to claim 6, characterized in that: The mass ratio of gelatin to chitosan is 1:0.5-2; the concentration of gelatin in the membrane matrix liquid is 0.05-0.1 g / mL.
8. The method for preparing aquatic product packaging film according to claim 6, characterized in that: The time for sufficient mixing is 15 to 30 minutes.
9. A packaging film for aquatic products prepared by the preparation method according to claim 1, characterized in that: The invention comprises a membrane matrix, a liposome loaded on the membrane matrix, and titanium and zinc oxides contained in the liposome.
10. The packaging film for aquatic products according to claim 9, characterized in that: The components of the membrane matrix include one or more of polylactic acid, gelatin, chitosan, dextran, polyvinyl alcohol or sodium alginate.
Citation Information
Patent Citations
Preparation method for tea polyphenol lipidosome / lysozyme-chitosan slow-release coating used for retaining freshness of fish slices
CN109757551A
Fresh-keeping cold catalyst material as well as preparation method and application thereof
CN115918714A
Dispersion liquid of titanium oxide-based antibacterial / deodorizing agent, and fiber and fabric having titanium oxide-based antibacterial / deodorizing agent applied thereon
JP2013047396A
An electrolyte composition containing zinc and silicon in a plasma electrolytic oxidation process and a method for manufacturing dental implants coated by hydroxyapatite containing zinc and silicon ions using the composition
KR101835684B1
Titanium dioxide sterilization and disinfection film
WO2022116005A1
